Impact of Biofield Energy Treatment Based Test Formulation on Vital Organ Health Specific Biomarkers Using Cell Line Study - Esmene Afaganis, Ariadne; Kumar Trivedi, Mahendra; Branton, Alice; Trivedi, Dahryn; Nayak, Gopal; Gangwar, Mayank; Jana, Snehasis (Journal of Tissue Repair and Regeneration, 2019)
Multiple organ dysfunction syndrome or failure is one of the major concerns against healthcare services in order to maintain the normal function. The present study aimed to explore the impact of the Biofield Energy Treated test formulation on the function of vital organs such as bones, heart, liver, lungs, and brain using standard activity parameters in specific cell-based assays. The test formulation and cells medium was divided into two parts, one untreated (UT) and other part received the Biofield Energy Treatment remotely by a renowned Biofield Energy Healer, Ariadne Esmene Afaganis, Canada and was labeled as the Biofield Treated (BT) test formulation/media. The test formulation was tested for cell viability, and the data suggested that the test formulation was found safe and non-toxic against all the cell lines. Cytoprotective activity among the experimental groups showed a significant improved activity by 94.4% at 1 µg/mL in untreated medium (UT-Med) + Biofield Treated Test Item (BT-TI) group in human cardiac fibroblasts cells (HCF) cells, while 84.4% at 10 µg/mL in BT-Med + BT-TI groups in human hepatoma cells (HepG2), and 124% increased cytoprotective action at 1 µg/mL in UT-Med + BT-TI group in adenocarcinomic human alveolar basal epithelial cells (A549) cells as compared with the untreated test group. ALP activity in MG-63 cells was significantly increased by 85.9% at 10 µg/mL in the UT-Med + BT-TI group, while in Ishikawa cells showed maximum increased ALP activity by 59.2% at 0.1 µg/mL in BT-Med + BT-TI groups as compared to the untreated group. The percent protection of HCF (heart) cells (decreased of LDH activity) was significantly increased by 53% and 40.5% at 1 and 10 µg/mL concentrations respectively, in UT-Med + BT-TI group, while BT-Med + UT-TI group showed increased protection by 68.5%, 70.7%, and 16.8% at 0.1, 1, and 10 µg/mL respectively, and 86.5%, 62.5%, and 34.2% improved cellular protection at 0.1, 1, and 10 µg/mL respectively, in BT-Med + BT-TI group as compared to the untreated test group. The percent protection of HepG2 (liver) cells (decreased of ALT activity) was reported by 33.5%, 63.2%, and 99.2% at 10 µg/mL in the UT-Med + BT-TI, BT-Med + UT-TI, and BT-Med + BT-TI groups, respectively compared to the untreated group. Cellular protection of A549 (lungs) cells (increased of SOD activity) in terms of percentage was increased by increased by 39.8% (at 10 µg/mL), 44% (at 25.5 µg/mL), and 59.7% (at 25.5 µg/mL) in the UT-Med + BT-TI, BT-Med + UT-TI, and BT-Med + BT-TI groups, respectively compared to untreated group. Serotonin level was significantly increased by 59.2% (at 0.1 µg/mL), 190.3% (at 0.1 µg/mL), and 201% (at 1 µg/mL) in the UT-Med + BT-TI, BT-Med + UT-TI, and BT-Med + BT-TI groups, respectively compared to untreated in human neuroblastoma cells (SH-SY5Y). However, the relative quantification (RQ) of vitamin D receptor (VDR) was significantly increased by 159.1% (at 50 µg/mL), 212.7% (at 1 µg/mL), and 278.3% (at 10 µg/mL) in the UT-Med + BT-TI, BT-Med + UT-TI, and BT-Med + BT-TI groups, respectively as compared to the untreated in MG-63 cells. Thus, the present data concluded that the overall multiple organ health using various standard biomarkers in specific cell lines were significantly improved with respect to health of bones, heart, liver, lungs, and brain after treatment with the Biofield Energy treated test formulation (The Trivedi Effect®). Thus, it can be used as a complementary and alternative therapy approach against many multiple organ disorders such as coronary artery disease, arrhythmias, congenital heart disease, cardiomyopathy, cirrhosis, liver cancer, hemochromatosis, asthma, chronic bronchitis, cystic fibrosis, osteoporosis, etc.
Keywords: Biofield Energy Treatment; Test Formulation; Vital Organs; Cytoprotective; Cell Viability